Free zinc as a predictive marker for COVID-19 mortality risk - Maares, Maria; Hackler, Julian; Haupt, Alessia; Heller, Raban; Bachmann, Manuel; Diegmann, Joachim; Moghaddam-Alvandi, Arash; Schomburg, Lutz; Haase, Hajo (Nutrients, 2022)
Free zinc is considered to be the exchangeable and biological active form of zinc in serum, and is discussed to be a suitable biomarker for alterations in body zinc homeostasis and related diseases. Given that coronavirus disease 2019 (COVID-19) is characterized by a marked decrease in total serum zinc, and clinical data indicate that zinc status impacts the susceptibility and severity of the infection, we hypothesized that free zinc in serum might be altered in response to SARS-CoV-2 infection and may reflect disease severity. To test this hypothesis, free zinc concentrations in serum samples of survivors and nonsurvivors of COVID-19 were analyzed by fluorometric microassay. Similar to the reported total serum zinc deficit measured by total reflection X-ray fluorescence, free serum zinc in COVID-19 patients was considerably lower than that in control subjects, and surviving patients displayed significantly higher levels of free zinc than those of nonsurvivors (mean ± SD; 0.4 ± 0.2 nM vs. 0.2 ± 0.1 nM; p = 0.0004). In contrast to recovering total zinc concentrations (r = 0.706, p < 0.001) or the declining copper-zinc ratio (r = −0.646; p < 0.001), free zinc concentrations remained unaltered with time in COVID-19 nonsurvivors. Free serum zinc concentrations were particularly low in male as compared to female patients (mean ± SD; 0.4 ± 0.2 nM vs. 0.2 ± 0.1 nM; p = 0.0003). This is of particular interest, as the male sex is described as a risk factor for severe COVID-19. Overall, results indicate that depressed free serum zinc levels are associated with increased risk of death in COVID-19, suggesting that free zinc may serve as a novel prognostic marker for the severity and course of COVID-19.
Gesehen am 18.05.2022